THE RELATIONSHIP BETWEEN SOCIAL SUPPORT, WORKLOAD, AND WORK STRESS IN PT. X EMPLOYEES - Salsabila Rizqi Rosesanthy; Laili, Nurfi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: Work stress is an adaptive response influenced by individual characteristics and psychological processes, which arises from external situations or actions that put certain psychological and physical pressure on individuals. In a corporate environment, employees are often faced with various job demands. Social support plays a significant role in reducing the negative impact of stressful work or excessive workload. This support can come from coworkers, superiors, family, close friends, or the surrounding environment. The greater the support received by employees, the lower the level of work stress they feel. Excessive workload is one of the causes of decreased employee performance. High production demands with limited work deadlines can create excessive work pressure, potentially reducing productivity. Method: This study uses a quantitative correlational method, which aims to analyze the relationship between two or more variables through statistical processing of numerical data. Results: The results of the multiple correlation test show that there is a significant relationship simultaneously between social support and workload with work stress. This is indicated by the F Change Significance value of 0.003 which is smaller than 0.05 (p < 0.05). The correlation value (R) of 0.480 indicates that the relationship between the two independent variables with work stress has a fairly close relationship. Novelty: Based on the results of the study, it can be concluded that there is a significant relationship between social support and work stress in employees of PT. X. High social support plays an important role in reducing work stress levels. Conversely, low social support has the potential to increase work stress. Workload also has a significant relationship with work stress, where high workload tends to increase physical, emotional, and social stress on employees.